Forensic botany: who?, how?, where?, when?. Issue 2 (March 2023) - Kasprzyk, Idalia
Highlights: Botanical materials have potential to be used as forensic evidence. Forensic experts work with plant remains more frequently than with whole specimens. Pig carcasses are a common model for experiments in forensic mycology. Diatom tests can confirm a post-mortem drowning. Forensic botany is routinely used in the criminal investigations in few countries. Abstract: Plants are a good source of biological forensic evidence; this is due to their ubiquity, their ability to collect reference material, and their sensitivity to environmental changes. However, in many countries, botanical evidence is recognised as being scientifically. Botanical evidence is not mostly used for perpertration, instead it tends to serve as circumstantial evidence. Plant materials constitute the basis, among others, for linking a suspect or object to a crime scene or a victim, confirming or not confirming an alibi, determining the post-mortem interval, and determining the origin of food/object. Forensic botany entails field work, knowledge of plants, understanding ecosystem processes, and a basis understaning of geoscience. In this study, experiments with mammal cadavers were conducted to determine the occurence of an event. The simplest criterion characterising botanical evidence is its size. Therefore, macroremains include whole plants or their larger fragments (e.g. tree bark, leaves, seeds, prickles, and thorns), whereas microscopic evidence includes palynomorphs (spores and pollen grains), diatoms, and tissues. Botanical methods allow for an analysis to be repeated multiple times and the test material is easy to collect in the field. Forensic botany can be supplemented with molecular analyses, which, although specific and sensitive, still require validation.